2014
DOI: 10.1086/675988
|View full text |Cite
|
Sign up to set email alerts
|

Pentraxin‐3 and the Right Ventricle: The Multi‐Ethnic Study of Atherosclerosis–Right Ventricle Study

Abstract: BACKGROUND: Coarse particulate matter (PM 10-2:5) is primarily mechanically generated and includes crustal material, brake and tire wear, and biological particles. PM 10-2:5 is associated with pulmonary disease, which can lead to right ventricular (RV) dysfunction. Although RV characteristics have been associated with combustion-related pollutants, relationships with PM 10-2:5 remain unknown. OBJECTIVES: To quantify cross-sectional associations between RV dysfunction and PM 10-2:5 mass and components among old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In the prospective MESA-right ventricle study it was found that men without confirmed cardiovascular disease with impaired RV-SV, RV-EDV, RV-ESV and reduced right ventricular mass were more likely to develop selfreported dyspnoea over a follow-up period of 60 months [26]. Furthermore, correlations were detected between right ventricular volumes, mainly elevated RV-EDV, and right ventricular mass and obesity, varying intensity of physical activity and elevated levels of pentraxin-3 that is known to be a marker in left heart disease [27][28][29].…”
Section: Discussionmentioning
confidence: 86%
“…In the prospective MESA-right ventricle study it was found that men without confirmed cardiovascular disease with impaired RV-SV, RV-EDV, RV-ESV and reduced right ventricular mass were more likely to develop selfreported dyspnoea over a follow-up period of 60 months [26]. Furthermore, correlations were detected between right ventricular volumes, mainly elevated RV-EDV, and right ventricular mass and obesity, varying intensity of physical activity and elevated levels of pentraxin-3 that is known to be a marker in left heart disease [27][28][29].…”
Section: Discussionmentioning
confidence: 86%
“…The elevated PTX3 concentration correlated with increased RV mass and end-diastolic volume assessed by cardiac magnetic resonance, and higher RV mass was associated with a threefold increase in CV or heart failure-related deaths [31].…”
Section: Pentraxin-3mentioning
confidence: 89%
“…Other novel inflammatory biomarkers which are less well studied but of potential value include neopterin [97] and pregnancy-associated plasma protein-A [98] associated with vulnerable plaque features such as thin-cap fibroatheroma in CAD patients; growth differentiation factor-15, [99] galectin-3 binding protein [100] and fibrinogen [101] with prognostic potential; and pentraxin 3 [102] and Soluble ST2 [103] associated with risk factors for atherosclerosis respectively.…”
Section: Circulating Biomarkersmentioning
confidence: 99%